Preparation method and catalytic application of precisely-oriented Pt-M diatomic catalyst
The lattice defects in Mo/W-based polyacid were constructed by a precisely directed method, and a highly dispersed Pt-M diatomic catalyst was prepared, which solved the problem of easy agglomeration and dissolution of platinum-based catalysts in the hydrogen evolution reaction, achieved efficient and stable catalytic performance, and was suitable for a variety of catalytic reactions.
Patent Information
- Application Number
- CN202510080392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
Existing platinum-based catalysts show excellent performance in hydrogen evolution reactions, but due to the scarcity of platinum metal resources and the high surface energy of Pt single atoms, they are prone to agglomeration and dissolution, making it difficult to maintain stable catalysis for a long time, and cannot meet industrial needs.
By using a polyacid-acid-acid-precision method, the lattice defects left by Zn escape in Mo/W polyacid were constructed, and combined with the impregnation and drying steps, a highly dispersed Pt-M diatom catalyst was obtained, achieving multi-stage stable and efficient dispersion of Pt-M diatoms.
The catalyst exhibits excellent catalytic activity and stability in acidic and alkaline media, with a loading capacity reduced by 91%, and a hydrogen evolution overpotential reduced by about 90%. It is suitable for many catalytic fields such as hydrogen evolution, hydrogenation and water and gas reaction.
Smart Images

Figure CN119897132A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a preparation method of a precisely guided Pt-M (M=Co, La, Fe, Ni, Cu, Mn, etc.) diatomic catalyst and its catalytic application. Background Art
[0002] Platinum-based catalysts exhibit excellent performance in hydrogen evolution reactions, but the scarcity of platinum metal resources limits their widespread application. Single-atom catalysts reduce the amount of platinum loaded by maximizing the efficiency of atomic utilization. However, isolated Pt sites limit the linear relationship between the adsorption energies of intermediates, and the high surface energy of Pt single atoms causes them to easily agglomerate. In addition, Pt species are easily transferred or dissolved from carriers (such as carbides, oxides, etc.), making it difficult to maintain long-term stable catalysis and unable to meet industrial needs. Therefore, the development of Pt-M (M = Co, La, Fe, Ni, Cu, Mn, etc.) diatomic catalysts with high density and high dispersion has become the key to improving catalytic performance and stability.
[0003] Mo / W-based transition metal compounds can couple with Pt-M diatoms, thereby greatly improving the catalytic activity. Taking molybdenum carbide (Mo2C) as an example, Mo2C not only has the d-band contracted electronic properties of precious metals, but also the change in work function between Pt-M and Mo2C makes the catalyst exhibit excellent electrochemical hydrogen evolution performance in a wide pH range. In order to realize Pt-M diatoms on Mo2C supports without the company of Pt and M metal nanoparticles, we constructed highly discrete atomic-level vacancies on the Mo2C surface to achieve the regulation of the microscopic chemical environment of Pt-M. In this type of strategy, Mo / W-based compounds act as secondary supports to stabilize Pt-M diatoms through electron-metal interactions (EMSI). At the same time, Mo / W-based compounds act as links to induce axial coordination between Pt-M diatoms and nitrogen-doped carbon supports, extending the multi-level stabilization of Pt-M diatoms to three dimensions.
[0004] Polyacids (POMs) have a clear atomic composition and chemical structure and are a kind of multi-nuclear oxygen-containing clusters between the atomic and mesoscopic scales. Using polyacids as precursors, Mo / W-based compound nanoparticles with uniform size and high dispersion can be precisely constructed based on their clear molecular structure, and efficient Pt-M diatomic hydrogen evolution catalysts with large specific surface area, high catalytic activity and many active sites can be obtained.
[0005] In view of this, the present invention provides a preparation method of a Pt-M diatomic Pt-M@Mo / W@NC catalyst precisely guided by a polyacid and its catalytic application, which belongs to the technical field of catalysts. The present invention obtains a lattice-protected Pt-M diatomic catalyst after simple impregnation and drying steps through the lattice defects left by the sublimation of Zn in the Mo / W-based polyacid containing Zn-M. The catalyst has excellent catalytic activity and stability in both acidic and alkaline media. The preparation method and preparation process of the present invention are simple, easy to operate, and can be mass-produced. Such materials can be widely used in multiple catalytic fields such as hydrogen evolution, hydrogenation, and water-gas reaction. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a Pt-M diatomic catalyst through a multi-level stable catalyst, which utilizes the characteristics of Zn sublimation to obtain highly dispersed M-Mo / W-based compound lattice vacancies, and accurately induces Pt atoms into the defects, so that the Pt-M diatoms are uniformly and stably dispersed inside the Mo / W-based compound lattice, thereby improving the dispersion and exposure of the Pt-M diatomic sites while limiting the Pt-M diatoms from falling off during the catalytic process.
[0007] To realize the above catalyst design, the adopted technical solution includes the following steps:
[0008] (1) Synthesis of precursor complex:
[0009] The Zn-M-containing Mo / W-based polyacid is highly dispersed in a carbon carrier, reacted at room temperature, centrifuged, washed, and vacuum dried to obtain a precursor composite product A.
[0010] (2) Synthesis of specific atomic vacancies:
[0011] Subsequently, during the high-temperature pyrolysis process, Zn and other elements in product A escaped. The pyrolyzed sample was stirred in a 3M HCl solution, centrifuged, washed, and vacuum dried to obtain product B with atomic-level vacancies.
[0012] (3) Synthesis of diatomic catalyst Pt-M@Mo / W@C:
[0013] Product B is dispersed in a Pt-containing impregnation solution and continuously heated, stirred and dried to finally obtain a catalyst Pt-M@Mo / W@C having a Pt-M diatomic site.
[0014] In the method of the present invention, in step (1), the carbon carrier includes carbon-based materials such as carbon nanotubes, graphene, and hollow mesoporous carbon spheres;
[0015] The mass ratio of the Zn-M-containing Mo / W-based polyacid to the carbon support is in the range of 1:(2-3);
[0016] The solvent was deionized water, and the synthesis time was 12 h;
[0017] Wash with deionized water and anhydrous ethanol 2-3 times respectively;
[0018] The vacuum drying temperature was 60°C and the time was 12 h.
[0019] In the method of the present invention, the atmosphere for high temperature pyrolysis in step (2) is nitrogen, and the pyrolysis time is 2 hours;
[0020] The programmed temperature method was used, the pyrolysis temperature was 900°C, and the heating rate was 5°C·min -1 ;
[0021] Wash with deionized water and anhydrous ethanol 2-3 times respectively;
[0022] The vacuum drying temperature was 60°C and the time was 8 h.
[0023] In the method of the present invention, the impregnation step in step (3) is: fully dispersing the product B obtained in step (2) in a solvent, and adding a platinum-containing salt solution under continuous stirring;
[0024] The heating temperature was 135°C and the stirring time was 3h;
[0025] The solvent is ethylene glycol; the solvent of the Pt salt solution is water;
[0026] The mass ratio of added Pt to the mass ratio of product B is (1-1.5):(25-30)
[0027] Wash with deionized water and anhydrous ethanol 3-4 times respectively;
[0028] The vacuum drying temperature was 60°C and the time was 8 h.
[0029] The present invention provides a method for preparing a precisely guided Pt-M diatomic catalyst and its catalytic application, belonging to the technical field of catalysts. The present invention obtains a lattice-protected Pt-M diatomic hydrogen evolution catalyst through the lattice defects left by the escape of Zn in Mo / W-based polyacids after simple impregnation and drying steps. Taking hydrogen evolution application as an example, compared with the commercial 20% Pt / C catalyst, the loading amount of the catalyst is reduced by 91%, and the hydrogen evolution overpotential is reduced by about 90%, with the advantages of many active sites, high catalytic activity and good stability. The preparation method and preparation process of the present invention are simple, easy to operate, and can be mass-produced. The obtained catalyst is widely used in many fields such as hydrogen evolution, hydrogenation and water-gas reaction.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) Heteropolyacids are well-defined inorganic nanoclusters composed of multiple transition metals and oxygen atoms. They are excellent precursors for preparing bimetallic catalysts because they promote better synergy between different metals, can be combined with organic polymer supports, and have ideal dispersion after pyrolysis. The well-defined structure of heteropolyacids provides an ideal platform for regulating the microenvironment of active metals and plays a key role in clarifying the actual active sites of the catalyst.
[0032] (2) Zn atoms are dispersed around Mo / W atoms in a discrete state, leaving abundant atomic-level vacancies in the lattice of Mo / W-based compounds after pyrolysis. The cationic vacancies in this lattice can effectively anchor and further stabilize the Pt-M diatoms, achieving precise regulation of the diatomic microscopic coordination environment. In addition, the catalyst carbon support can axially coordinate the Pt-M diatoms. This strategy achieves multidimensional coordination of the Pt-M diatoms, protects the Pt-M double sites to the greatest extent, and avoids the common problems of metal dissolution, transfer, and agglomeration during long-term industrial hydrogen evolution processes. This method of anchoring diatoms with lattice vacancies is applicable to most transition metal materials and has a certain degree of universality.
[0033] (3) The Pt-M mass ratio in the Pt-M diatomic catalyst is only about 1.8wt%, and it exhibits excellent catalytic activity in both strong acid and strong base environments. Taking hydrogen evolution as an example, compared with the commercial high-load Pt / C (20wt%) catalyst, its overpotential is reduced by 90%. After continuous electrocatalytic hydrogen evolution for 60h at high current density, the catalyst can still maintain about 100% hydrogen evolution performance, which is expected to be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the preparation process of the precisely guided Pt-M diatomic Pt-M@Mo / W@NC water electrolysis hydrogen evolution catalyst proposed in the present invention.
[0035] Figure 2 It is an electron microscope photo of the Pt-M diatomic catalyst provided in Example 1, taking M=Co and WO2 as a W-based compound as an example. Among them, (a) is a high-resolution transmission electron microscope photo of the Pt-Co@WO2@C catalyst, (b) and (c) are high-resolution transmission electron microscope photos of the Pt-Co@WO2@C catalyst at different magnifications, (d) is a high-angle annular dark field scanning transmission electron microscope image of the catalyst in a dark field, and (e) is a regional surface element distribution image of the Pt-Co@WO2@C catalyst. Figure 2 As shown in (a), the catalyst shows abundant lamellar and pore structures, which can promote the mass transfer efficiency in the hydrogen evolution process; Figure 2 (b)
[0036] Figure 3The linear sweep voltammetry (LSV) polarization curves of the reference catalysts with different active components and the commercial 20% Pt / C catalyst provided in Examples 1 to 6 under acidic conditions. It can be seen that the Pt-Co diatomic catalyst with designed atomic vacancies exhibits the best electrochemical hydrogen evolution activity with a current density of 100 mA cm -2 The overpotential is about 23 mV, which is much higher than 101 mV of the commercial 20% Pt / C catalyst, but the Pt loading is only 9% of that of the 20% Pt / C catalyst.
[0037] Figure 4 The linear sweep voltammetry (LSV) polarization curves of the reference catalysts with different active components and the commercial 20% Pt / C catalyst provided in Examples 1 to 6 under alkaline conditions. It can be seen that the Pt-Co diatomic catalyst with designed atomic vacancies exhibits the best electrochemical hydrogen evolution activity with a current density of 100 mA cm -2 The overpotential is about 70 mV, which is much higher than the 150 mV of the commercial 20% Pt / C catalyst, but the Pt loading is only 1 / 10 of that of the 20% Pt / C catalyst.
[0038] Figure 5 This is a further catalytic performance comparison between the Pt-M diatomic catalyst with designed atomic vacancies provided in Example 1 and the commercial 20% Pt / C catalyst. Figure 5 (a) shows the comparison of the hydrogen evolution mass activity per unit Pt of the atomic vacancy Pt-Co diatomic catalyst and the commercial 20% Pt / C catalyst under acidic conditions. Figure 5 (b) shows the comparison of turnover frequency (TOF) values of Pt-Co diatomic catalyst and commercial 20% Pt / C catalyst. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to more clearly understand the technical scheme of the present invention, the technical scheme and technical effect of the present invention are further illustrated below in conjunction with embodiments, and detailed implementation schemes and specific operating processes are provided. The following embodiments are used to illustrate the present invention, but are not limited to limiting the scope of the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. The described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work belong to the scope of protection of the present application.
[0040] Examples 1 and 2
[0041] This embodiment provides a method for preparing a precisely guided Pt-M diatomic hydrogen evolution catalyst. Since there are many schemes involved, one of the schemes of the above-mentioned method (M=Co, WO2 is a W-based compound) is taken as an example. The preparation method includes the following steps:
[0042] (1) Synthesis of precursor complex: 0.225 g Na 12 [Co2ZnW(ZnW9O 34 )]·48H2O was dissolved in 50mL of deionized water as solution A. 0.35g of cyanuric acid and 0.30g of melamine were dispersed in 200mL of deionized water as solution B. Solution A was added to solution B, reacted at room temperature for 12h, centrifuged, and washed with deionized water and anhydrous ethanol for 2-3 times in sequence. The washed product was placed in an oven at 60°C and vacuum dried for 12h to obtain a precursor composite product A.
[0043] (2) Constructing specific atomic vacancies: Subsequently, the dried solid particles of product A were ground and placed in a tube furnace. The heating rate was set to 5 °C min in a nitrogen atmosphere. -1 , heated to 900°C, kept warm for 2 hours, and cooled naturally to obtain a black powder. The black powder sample after pyrolysis was stirred in a 3M HCl solution for 3 hours and then centrifuged, and washed with deionized water and anhydrous ethanol for 2-3 times in sequence, and the washed product was placed in an oven at 60°C for 8 hours under vacuum to obtain a Co-WO2@C catalyst with atomic vacancies, as Example 2.
[0044] (3) Synthesis of diatomic catalyst Pt-Co@WO2@C: First, Na2PtCl6·6H2O was dissolved in deionized water to obtain 5 g·L -1 Na2PtCl6 solution was prepared, which was recorded as solution C. 50 mg of product B was dispersed in 15 mL of ethylene glycol solvent, 1 mL of solution C was added during stirring, and the mixture was heated to 135°C and stirred for 3 h before centrifugation. The mixture was washed with deionized water and anhydrous ethanol for 3-4 times in sequence, and the washed product was placed in an oven at 60°C and vacuum dried for 8 h to finally obtain a catalyst Pt-Co@WO2 having a Pt-Co diatomic site, as Example 1.
[0045] (4) Catalytic performance test: 0.5M H2SO4 solution and 1.0M KOH solution were used as electrolytes, a glassy carbon electrode with a diameter of 3mm was used as the working electrode, a graphite electrode was used as the counter electrode, and a silver chloride electrode and a mercuric oxide electrode were used as the reference electrode. A Gamry INTERFACE 1010E electrochemical workstation was used for the electrochemical hydrogen evolution three-electrode test. The electrode slurry preparation process was as follows: 5mg of the catalyst was dispersed in 1mL of ethanol and 20μL of 15wt% Nafion solution and ultrasonicated for 1h to obtain a uniform slurry, and 10μL of the slurry was applied to the surface of the glassy carbon electrode.
[0046] Example 3
[0047] (1) Synthesis of precursor complex: 0.225 g Na 12 [Co2ZnW(ZnW9O 34 )]·48H2O was dissolved in 50mL deionized water, and then 0.50g of melamine was added. After reacting at room temperature for 12h, the mixture was centrifuged and washed with deionized water and anhydrous ethanol for 2-3 times in sequence. The washed product was placed in an oven at 60°C and vacuum dried for 12h to obtain a white precursor powder.
[0048] (2) Synthesis of Pt-Co@WO2 catalyst: Then, the dried white solid particles were ground and placed in a tube furnace. The heating rate was set to 5 °C min in a nitrogen atmosphere. -1 , heated to 900℃, kept warm for 2h, and cooled naturally to obtain black powder. The black powder sample after pyrolysis was stirred in 3M HCl solution for 3h and then centrifuged, and washed with deionized water and anhydrous ethanol 2-3 times in sequence. The washed product was placed in an oven at 60℃ and vacuum dried for 8h to obtain black powder. 50mg of the above black powder was dispersed in 15mL ethylene glycol solvent, and 1mL 5g·L -1 The mixture was heated to 135°C and stirred for 3 hours, then centrifuged and washed with deionized water and anhydrous ethanol for 3-4 times. The washed product was placed in an oven at 60°C and vacuum dried for 8 hours to obtain the Pt-Co@WO2 catalyst.
[0049] (3) Catalytic performance test: Same as Example 1.
[0050] Example 4
[0051] (1) Synthesis of precursor complex: 0.35 g of cyanuric acid and 0.30 g of melamine were dispersed in 200 mL of deionized water, reacted at room temperature for 12 h, and then centrifuged. The mixture was washed with deionized water and anhydrous ethanol for 2-3 times in sequence. The washed product was placed in an oven at 60° C. and vacuum dried for 12 h to obtain a white precursor powder.
[0052] (2) Synthesis of Pt-Co@C catalyst: Then, the dried white solid particles were ground and placed in a tube furnace. The heating rate was set to 5 °C min in a nitrogen atmosphere. -1 , heated to 900℃, kept warm for 2h, and cooled naturally to obtain black powder. Disperse 50mg of the above black powder in 15mL of ethylene glycol solvent, add 1mL of 5g·L -1 Na2PtCl6 solution and 1mL 2g·L -1 The CoCl2 solution was continuously heated to 135°C and stirred for 3 hours, then centrifuged and washed with deionized water and anhydrous ethanol for 3-4 times in sequence. The washed product was placed in an oven at 60°C under vacuum and dried for 8 hours to finally obtain the Pt-Co@C catalyst.
[0053] (3) Catalytic performance test: Same as Example 1.
[0054] Examples 5 and 6
[0055] (1) Synthesis of precursor complex: 0.225 g Na 12 [La2ZnW(ZnW9O 34 )]·48H2O was dissolved in 50mL of deionized water as solution A. 0.35g of cyanuric acid and 0.30g of melamine were dispersed in 200mL of deionized water as solution B. Solution A was added to solution B, reacted at room temperature for 12h, centrifuged, and washed with deionized water and anhydrous ethanol for 2-3 times in sequence. The washed product was placed in an oven at 60°C and vacuum dried for 12h to obtain a precursor composite product A.
[0056] (2) Synthesis of La-WO2@C: Then, the dried solid particles of product A were ground and placed in a tube furnace. The heating rate was set to 5 °C min in a nitrogen atmosphere. -1 , heated to 900°C, kept warm for 2 hours, and cooled naturally to obtain a black powder. The pyrolyzed black powder sample was stirred in a 3M HCl solution for 3 hours and then centrifuged, and washed with deionized water and anhydrous ethanol for 2-3 times in sequence, and the washed product was placed in an oven at 60°C and vacuum dried for 8 hours to obtain a Co-W2N@NC catalyst, as Example 5.
[0057] (3) Synthesis of Pt-La@WO2@C: 50 mg La-WO2@C was dispersed in 15 mL ethylene glycol solvent and 1 mL 5 g·L -1 The Na2PtCl6 solution was continuously heated to 135°C and stirred for 3 hours, then centrifuged and washed with deionized water and anhydrous ethanol for 3-4 times in sequence. The washed product was placed in an oven at 60°C and vacuum dried for 8 hours to finally obtain a Pt-La@WO2@C catalyst, as Example 6.
[0058] (4) Catalytic performance test: Same as Example 1.
Claims
1. A method for preparing a precisely guided Pt-M (M = Co, La, Mn, Ru, etc.) diatomic catalyst, characterized in that: The following steps are involved: (1) Synthesis of a precursor composite: Mo / W-based polyacid containing Zn and M is highly dispersed in a carbon support, reacted at room temperature, centrifuged, washed, and vacuum dried to obtain a precursor composite product A; (2) Synthesis of specific atomic vacancies: Subsequently, during the high-temperature pyrolysis process, the Zn element in product A escapes. The pyrolyzed sample is stirred in a 3M HCl solution, centrifuged, washed, and vacuum dried to obtain product B with atomic vacancies; (3) Synthesis of Pt-M diatomic catalyst Pt-M@Mo / W@C: Product B is dispersed in an impregnation solution containing Pt, and then continuously heated, stirred and dried to finally obtain a catalyst Pt-M@Mo / W@C having a Pt-M diatomic site.
2. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (1), the carbon carrier includes carbon-based materials such as carbon nanotubes, graphene, and hollow mesoporous carbon spheres.
3. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (1), the mass ratio of the Mo / W-based polyacid containing Zn and M to the carbon carrier is in the range of 1:(2-3); the solvent is deionized water, and the synthesis time is 12 hours.
4. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (1), the product is washed with deionized water and anhydrous ethanol for 2-3 times respectively; the vacuum drying temperature is 60° C. and the time is 12 hours.
5. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (2), the high-temperature pyrolysis atmosphere is nitrogen, and the pyrolysis time is 2 hours; a programmed temperature method is adopted, the pyrolysis temperature is 900°C, and the heating rate is 5°C / min.
6. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (3), the impregnation process is specifically as follows: the product B obtained in the step (2) is fully dispersed in a solvent, and a salt solution containing Pt is added under continuous stirring.
7. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In step (3), the solvent is ethylene glycol; the Pt-containing solvent is water, and the specific concentration depends on different Pt salts. For example, 5 g·L -1 Na2PtCl6 solution; heating temperature is 135℃, stirring time is 3h.
8. The method for preparing a precisely guided Pt-M diatomic catalyst according to claim 1, characterized in that: In the step (3), the mass ratio of added Pt to product B is (1-1.5):(25-30).
9. A precisely guided Pt-M diatomic catalyst as described in any one of claims 1-14.